Dust impact on photovoltaic/thermal system in harsh weather conditions. (October 2022) - Kazem, Hussein A.; Chaichan, Miqdam T.; Al-Waeli, Ali H.A.; Al-Badi, Reem; Fayad, Mohammed A.; Gholami, Aslan
Highlights: Dust and pollutants accumulated in the PVT system were investigated. The dust accumulation and cleaning effects on PVT system performance were evaluated. Comparisons with PV modules and thermal collectors are presented. After 30 days of exposure to outdoor conditions, the percentage of energy generated per day was 61.17 %, 46.96 %, and 42.73 % for clean, polluted, and conventional systems, respectively. After 60 days of exposure to outdoor conditions, the average daily energy generated was 60 %, 38.18 %, and 33.9 % for clean, polluted, and conventional systems, respectively. Abstract: Dust causes losses in power generated by the PV modules as well as causes an increase in their temperatures. In this study, the photovoltaic/thermal (PVT) module dust heating effect was investigated using a spiral coil using for two PVT water cooling systems. One of the two systems was cleaned periodically (every-two weeks) and the second was left polluted with dust. The practical tests were conducted in Sohar – Oman outdoor conditions for two months (July and August 2021). The two systems performance was compared with a PV module left without cleaning. The dust accumulated on the studied systems caused a decrease in their average productivity. After 30 days, the clean PVT, polluted PVT, and conventional PV systems; yield was 61.17 %, 46.96 %, and 42.73 %, respectively. After 60 days, the average daily energy generated was 60.00 %, 38.18 %, and 33.90 % for clean, polluted, and conventional systems, respectively. Increasing the exposure period to external conditions caused an increase in the accumulated dust rate, resulting in a deterioration in the power output of both polluting PVT and conventional PV. In the periodic cleanliness of the PVT system, most of its performance was restored and its losses were limited. After 4 and 8 weeks, the yield losses for the conventional PV system were (9 % and 20 %), (2.5 %, 3.3 %) for the clean PVT system, and for the polluted PVT system they were (7.5 %, 17.7 %).